Richard Wallach family papers - Wallach, Richard, 1816-1881.
Chiefly correspondence of Wallach and other members of his family relating to national and local politics. Correspondents include John Quincy Adams, David Sherman Boardman, Luther Bradish, Orville Hickman Browning, James A. Buchanan, Thomas Corwin, William J. Duane, Millard Fillmore, John Forsyth, John Frothingham, Washington Irving, Ezekiel King, Henry Lee, Meriwether Lewis, Abraham Lincoln, James K. Polk, William Rawle, Caleb Smith, George W. Smith, William Swetland, Roger Brooke Taney, Arthur Tappan, Tobias Watkins, and Nathan Williams.
In part, negative photocopies.
Lawyer, Whig Party member, and mayor of Washington, D.C.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Adams, John Quincy, -- 1767-1848 -- Correspondence; Boardman, David Sherman, -- 1768-1864 -- Correspondence; Bradish, Luther, -- 1783-1863 -- Correspondence; Browning, Orville Hickman, -- 1806-1881 -- Correspondence; Buchanan, James, -- 1791-1868 -- Correspondence; Corwin, Thomas, -- 1794-1865 -- Correspondence; Duane, William J. -- 1780-1865 -- Correspondence; Fillmore, Millard, -- 1800-1874 -- Correspondence; Forsyth, John, -- 1780-1841 -- Correspondence; Frothingham, John, -- 1750-1826 -- Correspondence; Irving, Washington, -- 1783-1859 -- Correspondence; King, Ezekiel -- Correspondence; Lee, Henry, -- 1756-1818 -- Correspondence; Lewis, Meriwether, -- 1774-1809 -- Correspondence; Lincoln, Abraham, -- 1809-1865 -- Correspondence; Polk, James K. -- 1795-1849 -- Correspondence; Rawle, William, -- 1788-1858 -- Correspondence; Smith, Caleb, -- 1786-1870 -- Correspondence; Smith, George W. -- 1800-1876 -- Correspondence; Swetland, William, -- 1782-1864 -- Correspondence; Taney, Roger Brooke, -- 1777-1864 -- Correspondence; Tappan, Arthur, -- 1786-1865 -- Correspondence; Wallach family; Watkins, Tobias, -- 1780-1855 -- Correspondence; Williams, Nathan, -- 1773-1835 -- Correspondence; Whig Party (U.S.); United States -- Politics and government -- 19th century; Washington (D.C.) -- Politics and government -- 19th century; Lawyers; Mayors -- Washington (D.C.)